Chronic use of diazepam in primary healthcare centers: user profile and usage pattern - Ribeiro, Carmen Sylvia; Azevedo, Renata Cruz Soares; Silva, Viviane Franco da; Botega, Neury José (São Paulo Medical Journal, 2007)
CONTEXT AND OBJECTIVE: Chronic use of benzodiazepines is frequent in general practice. The aim of this study was to describe the usage pattern and profi le of chronic users of diazepam who had been consuming this drug for a minimum of thirty-six months continuously. DESIGN AND SETTING: This was a descriptive study (survey and clinical assessment) at fi ve primary healthcare centers in Campinas, Brazil. METHODS: Psychotropic drug control books revealed 48 eligible patients. Among these, 41 were assessed by means of the Schedule for Clinical Assessment in Neuropsychiatry (SCAN), the Hospital Anxiety and Depression scale (HAD) and a questionnaire on usage pattern. RESULTS: Most patients were women (85.4%). The patients’ mean age was 57.6 years, and they were from the social strata C (39%), D (54%) and E (7%). The mean length of diazepam consumption was 10 years. The patients presented a lack of prescription compliance and had made frustrated attempts to stop using the drug. 55.5% said their doctor had never given any guidance on the effects of the drug. According to SCAN, 25 patients (61%) suffered from depressive disorders; only 12 cases of benzodiazepine dependence were detected by this instrument. CONCLUSION: There is a need to improve the detection and treatment of mental disorders, as well as to prevent inappropriate prescription and use of benzodiazepines. Diazepam dependence has distinctive characteristics that make it undetected by SCAN.